ABOUT THE NEED TO CREATE AN AGROBANK IN THE MODERN REALITIES OF KAZAKHSTAN - B.Zh. Ahmetov; G.K. Musayeva; Zh.S. Tenizbayeva; E.Z. Kerimkulova; Zh.Zh. Sarkulova (Academic Journal of Physical and Chemical Sciences, 2019)
Identified problems regarding financing of agriculture. Industry funding has plummeted compared to historical retrospectives. Investment and innovation development, in order to achieve results, must be financed accordingly. Agricultural management is fraught with risks, poor infrastructure with a low population density, and the lack of accounting due to legislative norms makes the development of rural financial institutions inexpedient and risky. Existing government programs aimed at supporting both the agricultural industry and the financial sector set different and necessary goals. The financing of agricultural groups must, as well as respect the rights of large and small farmers, and not contradict the norms of the World Trade Organization, which includes Kazakhstan. Both the opinion of domestic experts and the experience of foreign countries suggest that Kazakhstan needs a specialized agro-industrial bank. Moreover, it is advisable to introduce a particularly legal framework for such a mechanism of financial activity, such as the Development Bank of Kazakhstan. After all, an ordinary commercial bank can either engage in currency speculation, or "send funds inappropriately." The conclusion is analyzed. The creation of a special level of the banking system, together with a political decision and special control by regulators, should solve many accumulated issues and problems in the industry. Indeed, in developed countries such a mechanism solves issues with overproduction, and in our realities there is a question of saturating the market with its products, which is relevant in the context of import substitution and national food security.